The Financial Strategies in Budgeting Allowances of GRADE 12 Working Senior High Students at Bestlink College of the Philippines: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
This study aims to determine The Financial Strategies for Budgeting Allowances for Grade12 Working Students and help the working students with the help of proposed interventionand remediation.It was figured out that the Budgeting Daily allowances are the impacts that affect theirfinancial strategies. Furthermore, results showed that Mental Health is the challenge thatworking students face. Budgeting Daily allowance inadequate funds are the advantages andthe disadvantages of grade 12 working students, and with the help of proposedrecommendations to the disadvantages, it lessened the challenges of grade 12 workingstudents. The respondents of the study were 50 selected grade 12 working students. Theselected respondents are those who have a connection to our study, which is all about thefinancial strategies of grade 12 working students. Based on the results of the study, theproposed intervention and remediation of the financial strategies to the grade 12 workingstudents addressed above the cited impacts and helps working students in terms of (1)Budgeting Daily Allowance – it helps the students to recognize the expenses they must payfor them to allocate their money. (2) Healthy Mental Health - It helps the students have abetter sense of relief and calmness, knowing that they have a proper financial strategy. (3)Inadequate Funds – It helps the students understand that having inadequate funds meanshaving no financial means to pay expenses.The researchers recommend to working students that they should consider financialstrategies as a guide and engage easily with their allowance. Working students shouldconsider financial strategies to meet their goals of being able to pay for their expenses.Working students should also consider financial strategies as a motivation to prioritize theirneeds above anything else. The research helps researchers in a way that throughout thestudy, they acquire information that helps them to navigate the impacts of financial strategieson working students. Future researchers should recommend Budgeting Daily Allowances tohelp working students manage their financial strategies.
Keywords: Financial analysis